The Hollow Men - White, Thomas (Cross currents, 2015)
An essay on moral evil as a privatized self is presented. It discusses the challenge presented by moral evil, a definition of moral evil, reflections on the traditional problem of God and evil, thoughts on the Science of Evil, the moral evil depicted in a poem about the Hollow Men, and moral evil as the inverse of Buddhism.